Can Mandated Political Representation Increase Policy Influence for Disadvantaged Minorities? Theory and Evidence from India - Rohini Pande (BREAD Working Paper No. 024, 2003)
A\basic premise of representative democracy is that all those subject to policy should have a voice in its making. However, policies enacted by electorally accountable governments often fail to reflect the interests of disadvantaged minorities. This paper exploits the institutional features of political reservation, as practiced in Indian states, to examine the role of mandated political representation in providing disadvantaged groups influence over policy-making. I find that political reservation has increased transfers to groups which benefit from the mandate. This finding also suggests that complete policy commitment may be absent in democracies, as is found in this case.